2019
DOI: 10.1292/jvms.18-0705
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of 25 canine behavioral problems and relevant factors of each behavior in Japan

Abstract: Undesirable behaviors exhibited by dogs are called canine behavioral problems. Behavioral problems are common among dogs kept in ordinary homes; hence, veterinarians need to have sufficient knowledge of these problems, so as to advise owners. Among dogs kept in ordinary Japanese homes, only a few behaviors have been investigated regarding prevalence and relevant factors. To improve understanding of behavioral problems, a comprehensive survey is crucial. In this study, we distributed an online survey including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 32 publications
(54 reference statements)
1
14
2
1
Order By: Relevance
“…This result suggests that feline behavioral problems are common in Japan. We previously conducted a similar online survey targeting dog owners and found that 86.0% of dogs troubled their owners by their behaviors [35]. The prevalence of behavioral problems among cats revealed in the current study was slightly lower than that reported in our previous study of dogs.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…This result suggests that feline behavioral problems are common in Japan. We previously conducted a similar online survey targeting dog owners and found that 86.0% of dogs troubled their owners by their behaviors [35]. The prevalence of behavioral problems among cats revealed in the current study was slightly lower than that reported in our previous study of dogs.…”
Section: Discussioncontrasting
confidence: 76%
“…This difference may have been caused by a difference in the number of investigated behaviors between the two studies. Specifically, we investigated 17 feline behaviors in the present study, whereas 25 canine behaviors were surveyed in our previous study [35]. Including a greater number of behaviors would be expected to increase the percentage of respondents who report being troubled by at least one behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Impaired social functioning in dogs is not uncommon, although it is difficult to extract exact numbers from literature due to issues of terminology and the use of diagnostic categories that do not allow us to identify the underlying emotion of a behaviour [13,14]. Alternatively, anxiety disorders are often mentioned as part of behavioural problems, but most often-and with the exception of separation anxiety-they are grouped under a general category of "anxiety" rather than related to the presence of social or non-social stimuli [15][16][17]. For fear, the subdivision of social and non-social is made, but this generally pertains to unfamiliar people or dogs [18,19].…”
Section: Introductionmentioning
confidence: 99%